Analysis of Mathematical Communication Ability in Flat Side Room Building Materials Reviewed from Students' Learning Interests - Viona Masithoh; Nida Sri Utami (Eduvest - Journal of Universal Studies, 2025)
This study analyzes mathematical communication skills based on students' high, medium, and low interest in solving planar geometry arithmetic problems and assesses each of these talent indicators. Arithmetic communication skills allow students to understand and explain arithmetic concepts orally and in writing. Descriptive qualitative research was used in this study. This study involved eighth-grade students from SMP Negeri 2 Kartasura. Data was collected through written assessments, student interviews, and observations. The findings and conclusions of this study reveal that students' mathematical communication skills regarding flat-sided geometry materials are assessed based on their learning interests. The analysis of students' difficulties shows deficiencies in understanding and precision in dealing with flat-sided geometry problems. Further, the results showed that students' mathematical communication skills failed to meet the four specified indicators. Findings from the study interest questionnaire showed that more than 90% expressed interest in flat-sided geometry content.